Obesity and COVID-19 in children and adolescents: a double pandemic. - Brambilla, Ilaria; Delle Cave, Francesco; Guarracino, Carmen; De Filippo, Maria; Votto, Martina; Licari, Amelia; Pistone, Carmelo; Tondina, Enrico (Acta Biomedica Atenei Parmensis, 2022)
Background and aim of the study. The high prevalence of obesity and obesity-related comorbidities has reached pandemic proportions, particularly in Western countries. It has been recently recognized as a significant risk factor in severe cases of COVID-19 in children and adolescents. Here, we summarize the existing knowledge regarding the pathophysiology of COVID-19 and consider how its various components may be exacerbated by the presence of obesity to investigate the impact of obesity on disease severity among patients with COVID-19 and collaborate for better clinical care of these patients.Methods. The literature search was conducted from March 2020 to January 2022. A review of articles was performed via the online database PubMed, combining the terms "obesity," "weight gain," "COVID-19", "children."Results. Excessive adipose tissue, insulin resistance, dyslipidemia, hypertension, high levels of proinflammatory cytokines are factors that compromise the functioning of organs and systems in obese patients. In obese patients with COVID-19 these changes can increase the risk of death, need for ventilatory assistance, risk of thromboembolism, and perpetuation of inflammatory response.Conclusions. Obesity increases the risk for hospitalization, intensive care admission, mechanic ventilation requirement, and death among children and adolescents with COVID-19. These findings emphasize the need for effective actions by health professionals to increase awareness of the risks resulting from obesity and how these are heightened in the current global pandemic.